Q Fever Endocarditis in Northeast Iran - Ali Akbar Heydari; Ehsan Mostafavi; Masoumeh Heidari; Mina Latifian; Saber Esmaeili (Case Reports in Infectious Diseases)
This report presents a case of chronic Q fever endocarditis. A 60-year-old male farmer and rancher was admitted to the hospital with symptoms of weight loss, fever, severe sweating, weakness, and anorexia. PCR was negative for C. burnetii in the blood sample, but phase I and II IgG antibodies against C. burnetii were positive (1 : 16384 and 1 : 2048, respectively) by the indirect immunofluorescent assay (IFA). According to the adjusted Duke criteria, Q fever endocarditis was confirmed, and the patient was successfully treated with doxycycline and hydroxychloroquine.